Strengthening Regional Identity Through The Management of The Museum Collection, Archives, and Building Sites of Malacca - Arif Rahman Bramantya; Irfan Rizky Darajat; Ikhtiar Anugrah Hidayat (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2021)
The history of Malacca as a port city has brought together the acculturation of cultures from various ethnicities. Thus, this is influencing the current image of Malacca and being dubbed The World Heritage City by UNESCO. This study aims to read the identity of the Malacca region represented through artifacts, archival management, archives stored in information institutions and building sites. The role of traditional institutions, the archival institution of the Malacca State Archives (ANM) and the Perbadanan Muzium Melaka (Perzim) in shaping a culture of memory through documentation work and archives management has a major impact on strengthening the identity of the Malacca region as an area with rich cultural values and historical narratives that surround it. In this case, cultural practices and documentation works are human rights so that it requires recognition from the government and society. This is also inseparable from the role of community, customary institutions and information institutions in safeguarding regional collective memory, preserving local wisdom and regional historicity through documentation work and holistic archives management. In general, the Malacca identity is deeply rooted in the social, economic, and cultural activities of the community.